2015
DOI: 10.1007/s00018-015-1939-6
|View full text |Cite
|
Sign up to set email alerts
|

The code of non-coding RNAs in lung fibrosis

Abstract: The pathogenesis of pulmonary fibrosis is a complicated and complex process that involves phenotypic abnormalities of a variety of cell types and dysregulations of multiple signaling pathways. There are numerous genetic, epigenetic and posttranscriptional mechanisms that have been identified to participate in the pathogenesis of this disease. However, efficacious therapeutics developed from these studies have been disappointingly limited. In the past several years, a group of new molecules, i.e. non-coding RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 118 publications
0
9
1
Order By: Relevance
“…We found that miR-34a was neither regulated by TGF-b1 nor did it modulate TGF-b1 profibrotic activity in lung fibroblasts, which contrasts with the features of most miRNAs that have been identified thus far to be involved in the pathogenesis of lung fibrosis (18,21,41). This study and previous investigations suggest that the activities of this special Figure 7.…”
Section: Discussioncontrasting
confidence: 73%
“…We found that miR-34a was neither regulated by TGF-b1 nor did it modulate TGF-b1 profibrotic activity in lung fibroblasts, which contrasts with the features of most miRNAs that have been identified thus far to be involved in the pathogenesis of lung fibrosis (18,21,41). This study and previous investigations suggest that the activities of this special Figure 7.…”
Section: Discussioncontrasting
confidence: 73%
“…First, lack of cell-specific delivery of miR mimics risks potential off-target effects caused by uptake of the mimics by cells that normally do not express the miRs (47). It is also critical for miR replacement/ reconstitution to restore their physiological levels, because miRs at supraphysiological levels could target gene sets that are quite different from those by miRs at endogenous levels, thus causing undesired side effects (48).…”
Section: Lentiviral Delivery Of Mir-27a-3p Attenuates Bleomycin-inducmentioning
confidence: 99%
“…For example, the direct inhibition of let-7d expression by TGF-β in AECs is associated with epithelial to mesenchymal transition and collagen deposition 68 . Similarly, several circulating miRNAs appear to be differentially expressed in the serum of IPF patients 67 . Moreover, the expression levels of miR-21, miR-155, and miR-101-3p in serum seem to be correlated with FVC and HRCT features of IPF 69 .…”
Section: Epigenetic and Microrna Regulation Phenotypingmentioning
confidence: 99%
“…Lung tissue miRNA profiling identified significantly increased 64 or decreased 65 levels of several regulatory miRNAs in IPF patients, thereby distinguishing the normal lung from the IPF lung and rapidly progressive from slowly progressive disease 66 . TGF-β seems to play a critical role in the upregulation of profibrotic miRNAs and downregulation of antifibrotic miRNAs 67 . For example, the direct inhibition of let-7d expression by TGF-β in AECs is associated with epithelial to mesenchymal transition and collagen deposition 68 .…”
Section: Epigenetic and Microrna Regulation Phenotypingmentioning
confidence: 99%